Effectiveness of patient decision aids for total hip and knee arthroplasty decision-making: a systematic review. Issue 10 (October 2021) - Pacheco-Brousseau, L.; Charette, M.; Poitras, S.; Stacey, D.
Summary: Objectives: To determine the effectiveness of patient decision aids (PtDAs) compared to alternative interventions (including usual care) on decision quality and quality of the decision-making process for adults with hip and knee osteoarthritis considering primary elective total joint arthroplasty. Methods: A systematic review guided by Cochrane methods and PRISMA reporting guidelines. Studies were searched in five databases. Included studies were RCTs evaluating the effect of PtDAs on total joint arthroplasty decision-making. Study quality was appraised with Cochrane's risk of bias tool. Quality and strength of recommendations were appraised with GRADE. Results: Ten included studies were conducted in North American using the same PtDA. Compared to usual care, PtDA groups demonstrated increased decision quality (e.g., higher knowledge, more informed values-based choices) and quality of the decision making process (e.g., decreased decisional conflict) (6 trials). Secondary outcomes showed increased surgeon satisfaction within the consultation and no difference in patient satisfaction or uptake of the chosen option (surgery: RR 1.03, 95% CI = 0.84 to 1.25; I 2  = 66%; 4 trials). When PtDAs formtats were compared, there were similar effects but no difference between PtDAs (4 trials). Conclusions: There was low to very low GRADE certainty of evidence for the effect of PtDAs on decision quality and quality of the decision-making process compared to usual care. No differences were found when different formats of PtDAs were compared (moderate to very low GRADE certainty of evidence).